(untitled) - Schweitzer, Felicia Cathrin

Algorithm selector for dynamic AGV scheduling in a smart manufacturing environment using machine learning (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.